Provisions of Using Chemical Drugs and their Derivatives in Islamic Jurisprudence (Islamic Sciences Journal, 2023)
ABSTRACT         Studies have shown that the use of chemical medications and their derivatives is prohibited because they result in self-killing and self-destruction. In fact, with the growth of chemical pharmaceuticals and their derivatives in recent times, worries have spread across the whole population. Islam has been keen to preserve the soul and the mind, physically and psychologically, in light of God's prohibition on killing the soul and the establishment of the death penalty. This is done in order to protect man from the evils of himself and to shield society from drug users, who pose a threat to other members of society. As Islamic Sharia's teachings and goals are all-inclusive, timely, and relevant to all concerns, they came with the ban of alcohol as one of many other items that are prohibited because they cause drunkenness and insanity. According to this, it is prohibited and unacceptable to use chemical medications and their derivatives. Just as alcohol was prohibited due to the serious damage it caused and the effects of its intake, so was the use of chemical drugs.
Keywords: Drugs, chemical, jurisprudence, legal provisions, addiction.